Do a company's sincere intentions with CSR initiatives matter to employees?: A comparison of customer-related and employee-related CSR initiatives. Issue 4 (8th October 2018) - Lee, Seoki; Lee, Kiwon; Gao, Yixing (Lisa); Xiao, Qu; Conklin, Martha
Abstract : Purpose: This study aims to examine how employees' perceptions of customer-related and employee-related corporate social responsibility (CSR) initiatives influence their job satisfaction. Further, the study investigates whether employees' organizational commitment mediates this proposed relationship and, more importantly, tests how such mediated relationships change according to the level of employees' perceptions of their company's sincerity in investing in CSR activities. Design/methodology/approach: This study used an online survey to collect data and collected a total of 490 responses for the main analysis. A regression analysis and standard path-analytic approaches described by Hayes (2013) were conducted to test the proposed hypotheses. Findings: Findings support the main effect of customer- and employee-related CSR on employees' job satisfaction mediated by employees' organizational commitment, as well as the moderating effect of the perceived sincerity of customer-related CSR but not employee-related CSR. Originality/value: The current study focuses on comparing two types of CSR initiatives, i.e. employee- and customer-related, because these two groups are any company's core stakeholders with the closest relationship to its operations, and they represent the internal and external stakeholders, respectively. Further, the current study investigates the moderating effect of employees' perceptions of the sincerity of their company's CSR initiatives on the relationship between the two types of CSR initiatives and employees' job commitment.